Growth of Pteropus alecto bats (Chiroptera: Pteropodidae) in cages - Tiltje Andretha Ransaleleh; Indyah Wahyuni; Martha Kawatu; Sylvia Laatung; Lucia Lambey; Unstain NWJ Rembet (Society for Indonesian Biodiversity, 2022)
Abstract. Ransaleleh TA, Wahyuni I, Kawatu M, Laatung S, Lambey L, Rembet UNWJ. 2022. Growth of Pteropus alecto bats (Chiroptera: Pteropodidae) in cages. Biodiversitas 23: 6313-6319. Black Flying Fox (Pteropus alecto), known as Paniki yaki, is widely consumed by the residents of Minahasa, North Sulawesi, Indonesia. It is imported from outside the provinces of Gorontalo, Central Sulawesi, and South Sulawesi. The peak of selling bats in Sulawesi is during Thanksgiving Day and religious holidays such as Easter, Christmas, and New Year. Even though the conservation status of this species, according to the International Union for Conservation of Nature (IUCN), is of Least Concern, this species will one day become extinct due to continuous exploration without control. Conservation or cultivation is one of the efforts to preserve this type of bat. Cultivation will be successful when the growth of this mammal is outside the habitat. Therefore, research has been conducted on breeding this animal in cages using five bats. The bats had been taken from the captivity in Wanea Sub-district, Manado city, 58-533 days old. The fruits given as food are papaya, banana, and mango, and the variables measured were the amount of consumption, body weight gain, and morphometry. Furthermore, the data obtained were tabulated and narrated descriptively. The results showed that consumption of P. alecto 1,2,3,4 and 5 fruits were 110.64, 147.86, 192.61, 249.18, and 331.61 g/day, with body weight gain of 0.50, 0.53, 0.96, 1, 17, 1, and 50 g/day. The morphometric growth of P. alecto 1 was total body length 0.10, forearm 0.06, tibia 0.03, ear 0.01 and wingspan 0.08 mm/day. Sequentially, the morphometric growth of P. alecto 2 was 0.11, 0.07, 0.05, 0.01 and 0.12 mm/day, while P. alecto 3 was 0.29, 0.13, 0.06, 0.03, and 0.89 mm/day. The growth of P. alecto 4 was 0.19, 0.02, 0.02.0.01 and 0.89 mm/day, while P. alecto 5 was 0.20, 0.01, 0.01, 0.01 and 0.85 mm/day. In conclusion, the 1st and 2nd P. alecto were in early bone growth, while the 3rd P. alecto was in bone and meat growth, meanwhile, the 4th and 5th P. alecto were in meat and slow bone growth.